From Judaism to Christianity : tradition and transition : a festschrift for Thomas H. Tobin, S.J., on the occasion of his sixty-fifth birthday - Tobin, Thomas H., 1945-; Walters, Patricia, 1947- (Novum Testamentum, Supplements, 2010)
As a far reaching tribute to the distinguished career of Thomas H. Tobin, S.J., a team of outstanding biblical scholars has joined to offer essays on the religious milieu of the ancient Mediterranean region. Challenged by Hellenistic and Greco-Roman cultural and political domination, the religious struggles of Jewish and, later, Christian communities sought to maintain tradition as well as mitigate transition. Jewish responses to a Hellenistic world are revealed anew in the Dead Sea Scrolls and the works of Artapanus and Philo. Also, Christian views on the transitory world of the early centuries of the Common Era are brought to light in the New Testament literature, apocryphal texts, and Patristic writings. Professors and students alike will benefit from the depth and breadth of this fresh scholarship.